Three new species of Acidiostigma Hendel (Diptera: Tephritidae: Trypetinae) and an updated key to species from the eastern Palaearctic and Oriental Regions - Chen, Xiaolin; Zhang, Lijie; Zhao, Mingshui (Zootaxa, 2016)
Three new species of Acidiostigma Hendel from China are described and illustrated. The new species are A. nigrofasciola Chen and Zhang, sp. nov., A. subpostsignatum Chen and Zhao, sp. nov. and A. tongmaiense Chen, sp. nov. An updated key to the known species of the genus is provided. The male of A. bimaculatum Wang and female of A. postsignatum (Chen) are newly recorded, described and illustrated. The biology and behaviour of A. bimaculatum Wang and A. postsignatum (Chen) are observed in the field and recorded for the first time.